Morphological and adhesive properties of Klebsiella pneumoniae biofilms - Lenchenko, Ekaterina (Vet World, 2020)
BACKGROUND AND AIM: The study of biofilm-forming ability of Gram-negative microflora has great practical importance for assessing the effectiveness of antibiotic therapy and finding new ways to diagnose and inhibit the growth of biofilms. This is because poor penetration of antibacterial drugs into the biofilm can lead to the selection of resistant strains and has a consequence evident by the occurrence of relapse of infection in animals. This study aimed to evaluate morphological and densitometric indicators of biofilm formation as well as adhesive properties of Klebsiella pneumoniae. MATERIALS AND METHODS: K. pneumoniae was cultured at 37°C for 2-144 h in vitro. The specimens for optical microscopy were prepared by fixation with a 1:1 alcohol-ether mixture for 10 min and stained with a 0.5% solution of gentian violet for 2 min, and the optical density index was evaluated at a wavelength of 490 nm. Further, the adhesive properties of the microorganisms were determined at a concentration of 1 billion/ml and a suspension of ram erythrocytes at a concentration of 100 million/ml when cultured at 37°C for 24 h. Blood smears were prepared and stained with 0.5% gentian violet. RESULTS: K. pneumonia cultured at 37°C after 24 h on the meat peptone agar formed large, convex, mucous, and white colonies (d=3.0-6.0 mm). With the growth in the meat and peptone broth, uniform turbidity of the medium was observed. Analyzing the optical density indices (density, D), it was found that K. pneumoniae were good producers of biofilms (D=0.528±0.31). Data for indicators of adhesive properties of K. pneumoniae were as follows: Average adhesion index, 4.56±0.14; adhesion coefficient, 1.07±0.52; and adhesion index, 4.26±0.07. The studied bacteria had high adhesive activity. A direct correlation dependence (R=0.94) of the optical density of biofilms (D≥0.514-0.551) and AAI (4.15±0.28-4.76±0.75) was established. CONCLUSION: This study has demonstrated that K. pneumoniae had high adhesive activity, was strong producer of biofilms, and the optical density of the sample exceeded the optical density of the control by more than 4 times.